Implementation Batu Local Govenmentâ€™s Agriculture Policy through Go Organic Programs in the Sustainable Agricultural Development ( Analytical Study on The System Thinking Method in Department of Agriculture and Forestry in Batu ). - Sumbayak, Piernando Hasudungan (Jurnal Administrasi Publik, 2013)
Abstrak: â€œImplementasi Kebijakan Pertanian Organik Wilayah Kota Batu Melalui Program Go Organic Dalam Menciptakan Pembangunan Pertanian Yang Berkelanjutanâ€. Revitalisasi lahan dalam program go organik berfungsi sebagai alternatif untuk meminimalkan dampak negatif dari kemajuan perkotaan. Tindakan ini bertujuan untuk menciptakan dan melestarikan lingkungan yang sehat dan menjaga keseimbangan ekologi. Kerusakan pada lahan pertanian mendorong pemerintah kota Batu untuk menerapkan strategi baru pada lahan pertanian dengan harapan dapat meningkatkan hasil pertanian dan menerapkan pertanian berkelanjutan. Pada tahun 2011 walikota merencanakan gerakan revitalisasi lahan yang diterbitkan dalam Perda No 7 tahun 2011 tentang penetapan lahan pangan berkelanjutan, pengumuman Walikota Kota Batu Â No. 1 tahun 2004 tentang Peremajaan Lahan dan No. 5 tentang Kepedulian Lingkungan dan Pertanian Organik Â pada tahun 2011 . Penelitian dilakukan dengan mengumpulkan data yang sesuai untuk memecahkan masalah yang ada. Metode penelitian diperlukan untuk mencapai hasil yang baik sesuai dengan tujuan penelitian. Metode penelitian umumnya dibagi menjadi dua , yaitu kuantitatif dan kualitatif. Penulis memilih untuk menggunakan penelitian kualitatif dengan metode System Thinking. System Thinking yang digunakan adalah sistem dinamis yang tidak stabil dan belum mencapai keseimbangan. Menentukan variabel / komponen dari fenomena dalam pemikiran sistem perlu untuk memperhatikan hal-hal berikut : Sistem di lingkungan ; disepakati atau ditentukan batas yang dari sistem itu sendiri , yaitu: Unsur ini ditemukan dalam sistem; Unsur luar sistem. Analisis Data Metode proses berpikir sistematis yang berlaku enam langkah ini secara berurutan akan menghasilkan peta atau model berpikir sistematis terpadu dan holistik . yang merupakan model elemen dasar sistem dari Program Go Organik tersebut. Abstract: Implementation Batu Local Govenmentâ€™s Agriculture Policy through Go Organic Programs in the Sustainable Agricultural Development ( Analytical Study on The System Thinking Method in Department of Agriculture and Forestry in Batu ). Revitalizing the lands in the way of organic program serves as an alternative to minimizing the negative impact of urban advancement. This course of action is aimed at creating and preserving healthy environment, and keeping the ecological balance. Assessing the extent of the damage to the farming lands prompted the municipality of Batu to apply new strategies to farming lands expecting to see an increase in yields and sustainable development in terms of agriculture. In 2011 the mayor planned out revitalizing movement which is issued in Local Regulation No. 7 year 2011 on the establishment of the sustainable crop lands, the mayorâ€™s announcement of Batu municipality No. 1 year 2004 on rejuvenation and No. 5 on environmental concern and organic farming in 2011. Investigation by collecting suitable data to solve problems. The research method is necessary to achieve good outcome in accord with the purpose of research. Therefore, the method is needed in conducting the research compatible with questions investigated. Research method is generally divided into two, namely quantitative and qualitative design. The writer chose to use qualitative research with system thinking method. System thinking used is dynamic systems that is unstable and has not yet reached equilibrium. Determining variables / components of a phenomenon in system thinking needs to heed the following: The system in an environment; TheÂ  agreedÂ  or prescribed limits of the system itself, namely:The element is found within the system;The element outside of the system. Data Analysis Methods Systematic thinking process that applies these six steps sequentially will generate a map or model of integrated and holistic systematic thinking. The previous complexity of systematic thinking requires tools for problem solving which is the basic element model of system thinking including. Keyword: revitalizing lands, organic farming, system thinking.